The past, present and future of light-gated ion channels and optogenetics - Sheena A Josselyn (eLife, 2018)
The discovery of the mechanisms underlying light-gated ion channels called channelrhodospins and the subsequent development of optogenetics illustrates how breakthroughs in science and technology can span multiple levels of scientific inquiry. Our knowledge of how channelrhodopsins work emerged from research at the microscopic level that investigated the structure and function of algal proteins. Optogenetics, on the other hand, exploits the power of channelrhodospins and similar proteins to investigate phenomena at the supra-macroscopic level, notably the neural circuits involved in animal behavior that may be relevant for understanding neuropsychiatric disease. This article is being published to celebrate Peter Hegemann, Karl Deisseroth and Ed Boyden receiving a 2018 Canada Gairdner International Award "for the discovery of light-gated ion channel mechanisms, and for the discovery of optogenetics, a technology that has revolutionized neuroscience".